Hemoglobinas anormales en una población estudiantil universitaria - Sáenz, German F. (1973)
Abnormal hemoglobins were found in 1.26% of 500 University of Costa Rica freshmen (1.06% A-S phenotype and 0.20% A-C) . An important factor is the discovery of 0.24% of abnormal hemoglobins, primarily due the S gene, in Caucasian Costa Rican students, or 0.5 % if three cases, apparently corresponding to a heterozygote beta thalassemia with a high F hemoglobin ( delta-beta variant), are included. Two asymptoma tic heterozygote phenotypes of persistent fetal hemoglobin (one in a white student an the other in a mulatto) were found among the abnormal hemoglobins. The differences between Costa Rican and foreign students, based on nationality and racial groups, are briefly commented.